دراسة تحليلية اقتصادية لتربية أسماك الكارب في المزارع السمكية بطريقة الأحواض الترابية في منطقة السقيلبية - درويش نضال (Latakia University Journal -Biological Sciences Series, 2019)
نتيجة للتزايد السكاني الكبير المتسارع, ازدادت الحاجة إلى إيجاد مصادر جديدة للغذاء، وهذا ما أكسب المصادر المائية أهمية خاصة في المساهمة بحل المسألة الغذائية, ونتيجة هذا الاهتمام تم التوجه نحو إنتاج أسماك المزارع في المياه العذبة . ولأهمية الأسماك بوصفها غذاءً عالي القيمة من النواحي الاقتصادية والغذائية والصحية، هدف هذا البحث إلى تحقيق الأهداف الآتية : تحليل الكُلَف الإنتاجية لتربية أسماك الكارب بطريقة الأحواض الترابية . التقويم الاقتصادي لتربية أسماك الكارب بطريقة الأحواض الترابية في منطقة السقيلبية . نتيجة الدراسة تبين أن أهم النتائج التي توصل إليها البحث هي : بلوغ صافي الربح المحقق في الدونم الواحد / 45216.35 / ل. س الكفاءة الإنتاجية المزرعية لتربية أسماك الكارب في منطقة السقيلبية 1.58. بلوغ الكفاءة الاقتصادية الإجمالية لتربية أسماك الكارب في منطقة السقيلبية 1.36 . بلوغ معامل الربحية قياساً بكلف الإنتاج 42.53 %, وقياساً برأس المال المستثمر 13.92%، وهو مؤشر جيد . Due to the increase and acceleration in population growth، need for providing new resources of food has escalated accordingly. This is what gives special importance to the water resources in contribution to solution of food problem. Within this concern comes the direction towards the fish farm production in fresh water. Since، fish has a high nutritive value from the economic، alimentary and sanitary trends، this Research has aimed to : analyze the productive costs of Carp Culture in Earthern ponds Method. evaluate economically Carp Culture in Earthern ponds Method. By conclusion, the study has reached the following important results : 1) The net profit achieved was ( 45216.35 )SYP/ 1000m2 2) The productive farm feasibility of Carp culture in Skelbieh Region amounted to /1.58/. 3) The total economical feasibility of Carp culture in Skelbieh Region amounted to /1.36/. 4) The Profitability Index as related to production costs amounted to 42.53% and as related to the invested capital amounted to 13.92%. This is a good indicator.